If it's not what You are looking for type in the equation solver your own equation and let us solve it.
18-3(-x)=2(-x)+3
We move all terms to the left:
18-3(-x)-(2(-x)+3)=0
We add all the numbers together, and all the variables
-3(-1x)-(2(-1x)+3)+18=0
We multiply parentheses
3x-(2(-1x)+3)+18=0
We calculate terms in parentheses: -(2(-1x)+3), so:We get rid of parentheses
2(-1x)+3
We multiply parentheses
-2x+3
Back to the equation:
-(-2x+3)
3x+2x-3+18=0
We add all the numbers together, and all the variables
5x+15=0
We move all terms containing x to the left, all other terms to the right
5x=-15
x=-15/5
x=-3
| 2=t4− 2 | | 2(5x-6)-2x=11-4x+1 | | -29=4+8(y+3) | | 15²=x(x+16) | | 2p−12=2 | | 2x+11=-2x-21 | | 8f-3+7=34 | | -5(2x-3)=2(x-13)-7 | | 14=-4+2z | | 2x+5(2x-5)=71 | | 5y/3=2y/3 | | 2+2x=3(-x+4)-20 | | 7x-9=8x-10 | | 5y/3-5/3=2y/3-5/3 | | 7y-9y+1=5 | | 4=k/2=-3 | | 16x-53=12x-37 | | /145=z/25 | | 2x+3-1=-x+8 | | /145=z25 | | 7y-9y=1=5 | | 2x+2=1x+10 | | 19a-98=14a-63 | | -52=4-8u | | 9x+72=4x+122= | | w+36=2w+29 | | 4b-59=2b-17 | | 11.02+0.8v=-0.7v−16.88 | | t=3t-62 | | s=6s-35 | | 9k=11k+14 | | r−15.9=−2.4 |